A DECOMPOSITION OF THE DECREASED STABILITY OF GDP, CONSUMPTION, INVESTMENT, GOVERNMENT EXPENDITURE, AND EXPORTS AND IMPORTS GROWTH IN ALBANIA - Kola, Blerim; Ndregjoni, Agim; Zerelli, Sonila; Gjermizi, Jehona (European Scientific Journal, ESJ, 2015)
In economics, the decrease or increase in economic growth is accompanied by the increase or decrease in GDP, Consumption, Investments, Government Expenditure, and Exports and Imports. By referring to the empirical data about GDP, Consumption, Investments, Government Expenditure, and Exports and Imports for the quarterly period from year 2000-2013, the main aim of this study is to explain how a shock to a variable is going to show the variability that can be expected during a period of time in the future. This article explores the impact of a shock in one variable to other variables and to itself. The evidence provided shows that most variability can be explained by the shock of two variables: consumption and investment. However, if the impact of a shock of GDP to GDP declines as time goes on, the impact of GDP shock on other variable is expected to increase. In conclusion, this article is based on the variance decomposition of variables included in other studies. However, even though changes is expected to be in other variables for all shocks of any variable, the investment and consumption components are responsible for most of the overall increase in volatility.